2023
DOI: 10.1021/acs.langmuir.3c00426
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Metallo–Organic Cage by Triphenylene-Cored Hexaterpyridine for Fast Iodine Capture

Abstract: In recent years, radioactive iodine capture has played an important role in nuclear waste treatment. However, most of the adsorbents possess low economic efficiency and undesirable reutilization in practical application. In this work, a terpyridine-based porous metallo−organic cage was assembled for iodine adsorption. Through synchrotron X-ray analysis, the metallo-cage was found to have a porous hierarchical packing mode with inherent cavity and packing channel. By taking advantage of polycyclic aromatic unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…14c). 64 This amorphous porous solid was used for iodine vapor adsorption and exhibited an I 2 adsorption capacity of 0.74 g g −1 after 40 h under ambient conditions. Moreover, compared to the amorphous powder of the nanocage, the Zn 12 L 4 crystal with huge channels displayed an ultrafast kinetic process of I 2 capture with a 94% removal efficiency after 5 min in water.…”
Section: Discrete Cagesmentioning
confidence: 99%
“…14c). 64 This amorphous porous solid was used for iodine vapor adsorption and exhibited an I 2 adsorption capacity of 0.74 g g −1 after 40 h under ambient conditions. Moreover, compared to the amorphous powder of the nanocage, the Zn 12 L 4 crystal with huge channels displayed an ultrafast kinetic process of I 2 capture with a 94% removal efficiency after 5 min in water.…”
Section: Discrete Cagesmentioning
confidence: 99%
“…The adsorbents reported include mainly silver-based solid adsorbents, activated carbons, metal-exchanged zeolite, clays, and others. Recently, new adsorbents with high surface areas and controllable porous structures, such as metal–organic frameworks (MOFs), covalent organic frameworks, porous aromatic frameworks, and other porous organic polymers, have been reported for iodine vapor capture. The adsorbent materials useable for capture of iodine from aqueous solution are not only limited, but also suffer from some shortcomings. For example, the nanomaterials-based adsorbents are easy to aggregate, which will decrease the accessibility of the binding sites. For porous materials-based adsorbents, the ratio of accessible binding sites are limited due to their unfavorable locations, the surface of internal pores. , Therefore, membrane separation technology has emerged as another method for the capture of iodine from aqueous solution because of their merits of high decontamination factor, large volume reduction, and low energy consumption. For instance, a polymer/MOF nanocomposite membrane was used for the quick removal of iodine from aqueous solutions. , …”
Section: Introductionmentioning
confidence: 99%
“…They can be assembled into a three-dimensional regular pore network, making them appealing for iodine capture. Previous studies on iodine adsorption have demonstrated that incorporating nitrogen-rich groups into the framework significantly improves the iodine adsorption capacity. However, the influence of the basicity of nitrogen species in POCs on iodine capture has not been explicitly investigated thus far.…”
Section: Introductionmentioning
confidence: 99%